A study on totally anisotropic Bianchi type-II space-time - Singh J.K.; Ram S. (My University, 2025)
Exact solutions of the totally anisotropic Bianchi type-II space-time are obtained in the scalar-tensor theories developed by Saez and Ballester (Phys. Lett. A, 113 (1985) 467) and Lau and Prokhovnik (Aust. J. Phys., 39 (1986) 339). The dynamical behaviour of these models has also been discussed.